ANALISIS PROSES PEMBAKARAN BERBASIS SIMULASI SOLIDWORK PADA MOTOR BENSIN 155,1 cc - Tegar Armanto; Sahal Sinatrya; M Raihan Ahsan; Noval Zuhaeri (Universitas Muhammadiyah Tangerang, 2023)
Due to limited resources and high expenses, simulation is a problem-solving technique that can assist in reducing the number of experimental experiments.Â The chosen combustion model significantly influences the simulation results.Â The practical strategy and research methodology on a 155.1 cc gasoline engine that uses combustion parameters requires using various combustion model parameters. In this study, a 115.1 cc gasoline engine's combustion process will be simulated, along with its production of exhaust gases in the combustion chamber. For a 155.1 cc petrol engine, our simulation uses SolidWork 2022 to identify the largest performance zone. The most significant performance zone for a 155.1 cc petrol engine is determined by our simulation using SolidWorks 2022. The output data is then compared at 5000, 6000, 7,000, 8,000, 9, and 10,000 revolutions per minute. According to the simulation results, a crank angle of 720.50 degrees and a rotational speed of 5000 rpm produce the ideal peak pressure for the best performance zone, which is 1497.20 kPa.